Microstructure and leaching characteristics of steel slag and CRT glass. Issue 1 (April 2020) - Mohamad, Ahmad Yusri; Jamil, Maslina; Md Yusoff, Nur Izzi; Fadzil, Syazwani Mohd
Abstract: In view of the large amount and types of waste materials generated, an extensive suite of environmental tests is carried out to assess the potential of reusing these materials. This study investigates the morphology and leaching characteristics of steel slag and Cathode Ray Tube (CRT) glass. The morphology and elemental composition of the samples are examined using field emission scanning electron microscope (FESEM) and energy dispersive X-Ray (EDX). The result of the leaching test is analysed and compared with the toxicity characteristics leaching procedure (TCLP) limit for hazardous elements. Results of the FESEM tests show that each sample has different morphological characteristics and texture. The surface of steel slag is rough, uneven, irregular and porous compared to the surface of granite and CRT glass. The outcome of the TCLP test shows that none of the identified hazardous elements exceed the standard limits, which indicates these materials may be suitable for use as construction materials.